TINDAK PIDANA PENCUCIAN UANG KLASIFIKASI DAN BENTUK SANKSI PIDANA BAGI KORPORASI - Vita Mahardhika (Fakultas Ilmu Sosial dan Humaniora, 2023)
Money laundering is an international phenomenon and challenge so that it is included in the category of extraordinary crimes. The perpetrators of money laundering crimes are individuals or corporations. In Law Number 8 of 2010 regulates the forms of activity that can be categorized as money laundering crimes and criminal sanctions imposed on perpetrators. In addition to the main criminal sanctions, there are additional penalties for corporations. Criminal sanctions for corporations certainly cause contraries because they are considered not to protect the rights of corporate workers who do not participate in committing criminal acts. This research is a normative legal research, analyzed through a statutory approach (statute approach) and a conceptual approach (conceptual approach) which refers to the philosophical basis for the formulation of Law Number 8 of 2010. The conclusion from this research is that in Law Number 8 of 2010 2010 contains the categorization of active and passive activities in the crime of money laundering and the harmful impact on national and international economic performance is the basis for the imposition of additional penalties for corporations.